Examining the influence of international large-scale assessments on national education policies - Fischman, Gustavo E.; Topper, Amelia Marcetti; Silova, Iveta; Goebel, Janna; Holloway, Jessica L. (Journal of education policy, 2019)
This paper examines whether, to what extent, and how international large-scale assessments (ILSAs) have influenced education policy-making at the national level. Based on an exploratory review of the research and policy literature on ILSAs and two surveys administered to educational policy experts, researchers, policymakers, and educators, our research found that ILSAs, with their multiple and ambiguous uses, increasingly function as solutions in search for the right problem - that is, they appear to be used as tools to legitimize educational reforms. The survey results pointed to a growing perception among stakeholders that ILSAs are having an effect on national educational policies, with 38% of respondents stating that ILSAs were generally misused in national policy contexts. However, while the ILSA literature indicates that these assessments are having some influence, there is little evidence that any positive or negative causal relationship exists between ILSA participation and the implementation of education reforms. Perhaps the most significant change associated with the use of ILSAs in the literature reviewed is the way in which new conditions for educational comparison have been made possible at the national, regional, and global levels.